The Distribution per capita of water in Ecuador (Revista Científica Ciencias Naturales y Ambientales, 2016)
The availability of water at global scale and the estimation of this resource per capita in the Ecuadorian mainland until 2016 are described. This paper is supported on the modular volumes estimated by the The National Water Secretary of Ecuador (SENAGUA) and the population data from the Census of Population and Housing conducted in Ecuador in the year 2010. The study showed that the overall availability of water per capita is within the range proposed by the World Bank; however, the present distribution is inequitable and deficient, especially in the province of Manabi and other regions of the coast of Ecuador, whose rivers are fed only by the rainfalls during the rainy season.
Keywords: Ecuador; hydrogeology; modular flows; hydric deficit; water